2023
DOI: 10.1101/2023.01.09.523139
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolutionary transcriptomics reveals longevity mostly driven by polygenic and indirect selection in mammals

Abstract: The maximum lifespan varies more than 100-fold in mammals. This experiment of nature may uncover of the evolutionary forces and molecular features that define longevity. To understand the relationship between gene expression variation and maximum lifespan, we carried out a comparative transcriptomics analysis of liver, kidney, and brain tissues of 106 mammalian species. We found that expression is largely conserved and very limited genes exhibit common expression patterns with longevity in all the three organs… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 155 publications
(199 reference statements)
0
4
0
Order By: Relevance
“…To generate the species-specific ortholog sets and calculate expression values, we downloaded the reference genomes of species (if available) from the public database. For those without a reference genome, Trinity was used to perform de novo assembly of transcripts [37] based on previously generated liver, kidney, and brain transcriptome to assemble transcripts [38]. The fixed parameter k-mer size was 25, the minimum contig length was 200, and the paired fragment length was 500.…”
Section: Rna-seq Sequencing Orthologous Gene Sets and Gene Expression...mentioning
confidence: 99%
“…To generate the species-specific ortholog sets and calculate expression values, we downloaded the reference genomes of species (if available) from the public database. For those without a reference genome, Trinity was used to perform de novo assembly of transcripts [37] based on previously generated liver, kidney, and brain transcriptome to assemble transcripts [38]. The fixed parameter k-mer size was 25, the minimum contig length was 200, and the paired fragment length was 500.…”
Section: Rna-seq Sequencing Orthologous Gene Sets and Gene Expression...mentioning
confidence: 99%
“…The natural variation in mammalian longevity and its underlying mechanisms remain an active area of aging research. In the latest issue of The EMBO Journal, Liu et al (2023) analyze gene expression levels in 103 mammalian species across three tissues, revealing tissue-specific associations between gene expression patterns and longevity. Remarkably, the study suggests that methionine restriction, a strategy shown to increase lifespan, may extend beyond artificial interventions and is similarly employed by natural selection.…”
Section: Evolutionary Paths To Mammalian Longevity Through the Lens O...mentioning
confidence: 99%
“…This highlights a shared strategy between natural selection and human-induced laboratory interventions, such as drug treatments or genetic manipulations, aimed at anti-aging and the regulation of lifespan. Liu et al (2023) present a combination of extensive data collection and an innovative approach to comparative genomics of aging by merging genomics and transcriptomics. Through the integration of diverse data from multiple species, they have laid a strong foundation for future studies.…”
Section: Evolutionary Paths To Mammalian Longevity Through the Lens O...mentioning
confidence: 99%
See 1 more Smart Citation